Types of Lexical Complexity in English: Syntactic Categories and the Lexicon - Anderson, John (Studia Anglica Posnaniensia, 2013)
This study focuses on minimal (non-compound, non-phrasal) signs that are nevertheless internally complex in their syntactic categorization. Sometimes this is signalled by morphology - affixation or internal modification. But there are also conversions. In terms of categorial structure, we can distinguish between absorptions, where the source of the base is associated with a distinct category, and incorporation, where the base is categorially constant. Incorporation is thus typically reflected in inflectional morphology. Absorption may be associated with morphological change or conversion - with retention of the base in a different categorization. But categorial complexity may be nonderived, covert: the categorial complexity of an item is evident only in its syntax and semantics.